Impact of monetary policy on bank loans in India - E. Kasana; K. Chauhan; B. P. Sahoo (Финансы: теория и практика, 2023)
This research paper aims to investigate the monetary transmission in India through bank lending channel, to know whether a change in monetary policy affects bank loans or not. A balanced panel data of 50 commercial banks covering a timeframe of 11 years from 2009 to 2020 has been undertaken for the research methodology. The outcomes of the dynamic panel have been considered by using the Generalized Method of Moment developed by Arellano Bond Blundell and Bover estimator. The result indicates that channel of bank lending has improved banks’ resilience to monetary shocks. This paper finds the significance of bank characteristics like size, liquidity, and capital which have a substantial impact on bank lending. This research study concludes that repo rate, cash reserve ratio and weighted average call rate are imperative instrument of monetary policy transmission. Banks with small size, capital, and liquidity are more sensitive to any variation in monetary policy as compared to large banks.